2004
DOI: 10.1038/sj.onc.1208319
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus latent membrane protein 1 represses p53-mediated DNA repair and transcriptional activity

Abstract: The latent membrane protein 1 (LMP1) of Epstein-Barr virus (EBV), a viral oncogene, is essential for transformation of resting B cells by the virus. We previously demonstrated that LMP1 could repress DNA repair in p53-wild-type and p53-deficient human epithelial cells. In this study, using a host cell reactivation (HCR) assay, we demonstrated that p53-enhanced DNA repair was repressed by LMP1 in p53-deficient cells. Moreover, we found that LMP1 was able to repress p53-dependent transcriptional activity. Regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 61 publications
(65 reference statements)
1
46
1
2
Order By: Relevance
“…It has been observed that expression of EBV LMP1 protein represses p53-mediated DNA repair and transcriptional activity through the activation of the NF-B pathway. This suggests that the abrogation of DNA repair by LMP1 may induce genomic instability and contribute subsequently to tumorigenesis (37,38). Here we propose that EBV BKRF3 may function in addition to LMP1 to contribute to genome instability, thus favoring AID/UNG-induced c-myc/IgH translocations.…”
Section: Discussionmentioning
confidence: 93%
“…It has been observed that expression of EBV LMP1 protein represses p53-mediated DNA repair and transcriptional activity through the activation of the NF-B pathway. This suggests that the abrogation of DNA repair by LMP1 may induce genomic instability and contribute subsequently to tumorigenesis (37,38). Here we propose that EBV BKRF3 may function in addition to LMP1 to contribute to genome instability, thus favoring AID/UNG-induced c-myc/IgH translocations.…”
Section: Discussionmentioning
confidence: 93%
“…Latent phase genes of EBV including Zta, LMP1, LMP2A, LMP2B. EBNA1, EBNA2, BGLF4, EBNA3C and truncated LMP1 genes (DX, DT, DBX, DS, D189-222, D189-321 and D350-389) were also sub-cloned into pSG5 expression vector (Liebowitz et al, 1992;Liu et al, 2005). The shRNAi sequences were shown as follows: 145-165, 5 0 -CTCCACTCCCTTCTCCAAAAG-3 0 and 1066-1086, 5 0 -CTGCCCAGTGTAGGTGTATTC-3 0 .…”
Section: Methodsmentioning
confidence: 99%
“…TW01 and HONE1 cells, human NPC cell lines, were maintained in Dulbecco's modified Eagle's medium supplemented with 10% fetal calf serum (Liu et al, 2005;Fang et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Data in cell culture indicate that LMP1 upregulates A20, which can block p53-mediated apoptosis (Laherty et al, 1992;Fries et al, 1996). Furthermore, LMP1 represses p53-mediated DNA repair and transcriptional activity and this activity is dependent on the NF-kB pathway (Liu et al, 2005). The presence of elevated p53 protein and lack of mutations in LMP1-positive mouse lymphomas suggests that LMP1 also affects p53 expression and function in vivo.…”
Section: Signaling and Activation Of Nf-jb In Lmp1 Transgenic Mice Njmentioning
confidence: 99%